PW 1457 Self-reported contributory factors for work-related injuries in qatar: findings from the WURQ in-patient survey. (November 2018) - Consunji, Rafael; Hirani, Nazia; Thomas, Sam; Luzano, Kristine; Mehmood, Amber; Abeid, Aisha; El-Menyar, Ayman; Al-Thani, Hassan; Mollazehi, Monira; Hyder, Adnan; Peralta, Ruben
Abstract : Introduction: Work related injuries (WRIs) are a leading cause of trauma admission in Qatar; their epidemiologic trends and high-risk populations have been reported. This study aims to explore the work circumstances and environments leading to severe WRIs, to inform the creation of targeted interventions to improve worker safety. It was conducted as part of a larger 'A Unified Registry for Workplace Injury Prevention in Qatar' grant [NPRP 7–1120–3–288], funded by the Qatar Foundation, designed to initiate and implement a unified workplace injury registry to inform policies and programs to reduce the health burden, in terms of deaths and disabilities, and the healthcare costs from WRI's. Methods: WRI patients who were admitted to the Hamad Trauma Center were interviewed by trained interviewers using a standard questionnaire. A proportionate sampling method was implemented based on the leading mechanisms of injuries. Results: Fifty patients were consented and interviewed. 58% had some kind of safety training and 82% were aware about the risks at work. Seventy eight percent used one form of personal protection: 58% -safety helmet, 62% -foot protection, 54% – high visibility jacket/vest and 50% – antistatic gloves. Approximately 50% of the patients had one form of health insurance. Almost everyone was given treatment on-site prior to being transported to the nearest treatment facility. Self-reported contributory factors, for WRI, included: 'inadequate training for a new task', 'sub-optimal working environment' and 'psychological factors'. Almost all classified their injuries as 'accidental' or unexpected. Conclusion: In this study population, WRIs are still thought of as 'accidental' by the workers themselves. Areas for improvement include: 1.) culturally appropriate safety training 2.) increased use and availability of personal protective equipment 3.) health insurance and 4.) training for new tasks. Further studies on knowledge and attitudes of workers towards safety are needed to better inform occupational injury prevention programs in Qatar.